Hubungan Antara Beban Kerja Dengan Keterlibatan Kerja - Jumalia Oktaviana, Dwi; , Drs. Mohammad Amir, M.Si (2016)
Every organization has a goal to achieve optimum performance, but still there are problems between them. According to the interviews on the two guards they say there are some employees are not fully engaged in completing the work because they think these jobs are heavy. Companies should look at the work engagement of each employee to put in a position to produce a maximum performance so that all work can be done properly. The purpose of this study (1) to determine the relationship between workload with job involvement, (2) to determine the level of workload, (3) to determine the level of job involvement, (4) to determine the role of the workload of the job involvement. This study uses a cluster of non-random sampling at BAU unit employees, Guidance and Counseling, Security Guard, Library, Faculty of engineering with the number of 60 people. Data collection tool that is used to obtain the data in this study is the scale of the workload and job involvement scale. Data analysis technique using Pearson Product Moment. Based on the analysis of product moment correlation indicates that there is a significant negative relationship between workload with job involvement. The workload is relatively low, while for work engagement is high. The workload of a role by 48.4% against the involvement of labor and the rest obtained from other variables.